Attributes of screening and vaccination for cervical cancer: insights of an online survey among female school teachers of Kota, Rajasthan, India - Aparajita Sharma; Bijit Biswas; Bhawna Sati (Tabriz University of Medical Sciences, 2021)
Background: Cervical cancer is largely preventable. The study was aimed to find out the attributes of screening and vaccination for cervical cancer among female school teachers of Kota, Rajasthan, India. Methods: It was an observational study, cross-sectional in design conducted among female school teachers of Kota, Rajasthan, India using a predesigned structured questionnaire administered by Google Form during the months of March to May, 2020. In total, 397 schoolteachers from 18 different schools of Kota participated in our survey. Results: Among the study subjects, 33 (8.3%) had ever undergone screening for cervical cancer, whereas only 12 (3.0%) had taken vaccine against it. In multivariable logistic regression analysis; age (>40 years) [adjusted odds ratio (AOR): 5.7 (2.0-15.8)], correct knowledge regarding frequency of screening (yes) [AOR: 6.0 (2.4-15.5)], positive attitude for the disease (yes) [AOR:3.0 (1.1-8.0)] and gynaecologist consultation behaviour (periodic) [AOR: 1.4 (1.1-8.6)] were significant attributes of ever undergoing screening for cervical cancer. On the other hand, themultivariable significant attributes of vaccination were age (≤40 years) [AOR: 7.6 (1.5-38.9)]and positive attitude for the disease (yes) [AOR: 6.4 (1.1-38.2)]. Conclusion: Acceptance of screening and vaccination for cervical cancer among the study subjects was found to be quite low. Policymakers should more actively involve school teachers in generating awareness and in raising the demand for cervical cancer screening and vaccination in their native communities to curb the disease in the country.